POSTOPERATIVE COMPLICATIONS AFTER RADICAL CYSTECTOMY AND THEIR INFLUENCE TO SURVIVAL AND POSTOPERATIVE MORTALITY - M. I. Kogan; O. N. Vasiliev; V. A. Perepechay (Медицинский вестник Юга России, 2014)
Purpose: to estimate the risk of postoperative complications and frequency of them after radical cystectomy and to study the specific parameters of influence to survival and postoperative mortality.Materials and methods: 311 patients with urinary bladder cancer were underwent RCE, bilateral pelvic lymphadenectomy and urinary diversion’s various methods.Results: there are various complications after RCE accompanyed with different methods of urinary diversion were registered in 82.0% of patients with bladder cancer. In 18.0% of patients with bladder cancer who underwent RCE there were no observed any complications. During an early follow-up period the average frequency of complications associated with the urine reservoir was not exceed than 6.75 per 100 patients, whereas in the later period of observation it increased to 11 times and reached 71.93 per 100 patients.Summary: Orthotopic methods of derivation were performed in 47,0% of patients with bladder cancer and external methods were used in 37,6%. Among patients with external and especially internal forms of derivation the worst survival rates and high rates of various kinds of complications were registered.